Un nuevo catálogo de pliegos sueltos de la imprenta de Agustín Laborda y Campo. - GOMIS COLOMA, JUAN (Scripta)
This article reports the discovery of a catalogue of pliegos sueltos published by the printer Agustín Laborda y Campo towards the end of his life. Catalogues are documents of extraordinary value for the history of books and printing, but their preservation is rare and their location is difficult. This is even more true in the case of chapbooks' catalogues, the known number of which is very small and mostly from the 19th century. Hence the value of the Memoria de los romances, relaciones, historias, entremeses, estampas iluminadas, libros y otras menudencias presented in this article: in addition to its digital reproduction, its contents are analysed in relation to Agustín Laborda's professional career and especially to an earlier catalogue from his workshop, unveiled by Jaime Moll in 1981. If the preservation of a catalogue of pliegos sueltos is a rarity in itself, having two published by the same printer is an extraordinary fact and constitutes an opportunity to study the evolution of the publishing strategies of typographers specialising in literatura de cordel.